A False Route Case of Primary Excision Anastomosis (EPA) Procedure in The Treatment of Traumatic Bulbar Urethral Stricture - I Gusti Ayu Putri Purwanthi; Gede Wirya Kusuma Duarsa; Tjokorda Gde Agung Senapathi (Indoscholar, 2019)
The bulbar urethra stricture is the most common form of anterior urethral stricture. The treatment of urethral strictures are varies and remains a challenging field in urology. Excision Primary Anastomosis (EPA) described as the most effective intervention for traumatic urethral stricture cases with a long-term success rate. This case report described male, 42 years old with history of pelvic injury. He had underwent cystostomy and conservative management for his pelvic injury. After EPA and pubectomy procedure in September 2019, he was still unable to void from his urethra. Radiologic evaluation with BVUC was done on October 2019, showing total obstruction of urethral as high as superior aspects of pars bulbosa, unfavourable anastomosed and displaced urethra. Acquired urethral stricture or fistula is an unexpected result of urethral reconstruction and leads to much inconvenience as well as psychological problem for the patient. This condition is avoidable by operation that was performed by experienced urologist and using a flexible cystoscopy as a guidance.